A directed search for QTL affecting carcass composition traits in Texel sheep : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Animal Science at Massey University, Palmerston North, New Zealand - Johnson, Patricia Lea (Massey University, 2003)
In New Zealand moves towards lean-meat yield- and meat quality-based payment of lamb carcasses, which more accurately reflect consumer preferences, mean that breeders and producers will need to change their selection objectives and management practices to maximise returns. This thesis investigates approaches to achieving increased meat yields, while not detrimentally affecting meat quality. The main objective was to search for Quantitative Trait Loci (QTL) affecting carcass composition traits in Texel sheep, in the region of Growth Differentiation Factor 8 (GDF8) on ovine chromosome 2. Dissection and meat quality data for legs and loins were collected for 90 Texel-cross progeny from each of six Texel or Texel-cross sires. All animals were genotyped for seven markers around GDF8. A QTL which increased leg muscle by 5-8% and decreased leg fat by 10-15% was identified for four of the six sires in the region of markers BM81124 and BULGE20. The two sires for which no QTL was detected, were homozygous and therefore uninformative at these markers. The QTL did not negatively affect meat quality. There was only limited evidence for a QTL affecting loin composition traits. Candidate genes to explain the QTL effect, in addition to GDF8, were sought, based on the conserved synteny between the ovine and human genomes, but none were identified. A number of genes in the region are poorly documented, and new genes are still being mapped to the region so a candidate gene could yet emerge. The progeny data set when analysed for sex differences, revealed that, relative to ewe lambs, meat from the ram lambs had 10% higher Warner-Bratzler shear values, was less red, and for M. longissimus, had 28% more samples that exceeded the "high pH" threshold of 5.8. These negative meat quality aspects for ram lambs need further investigation to determine their commercial importance. Future research on the putative QTL for leg and loin composition should assess its effects on other parts of the carcass, and its effect in lambs homozygous for the QTL. Additionally its position needs to be more closely defined, and ideally the specific gene or genes involved identified, before industry implementation is carried out.
Keywords: Sheep genetics; Sheep breeding; Sheep carcass composition; Texel sheep; Quantitative genetics; New Zealand; Fields of Research::300000 Agricultural, Veterinary and Environmental Sciences::300400 Animal Production::300401 Animal breeding